The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.18470/1992-1098-2016-3-106-119
|View full text |Cite
|
Sign up to set email alerts
|

Results of Long-Term (2006-2016) Avian Influenza Surveillance in Wild Birds of Uvs Nuur Lake

Abstract: Резюме. Цель: Проведение анализа результатов многолетнего мониторинга вируса гриппа птиц в одной из ключевой точек Северной Евразии -оз. Убсу-Нур, Республика Тыва. Методы. Проведен анализ доступных источников и результатов собственных исследований. Для построения филогенетической дендрограммы использована программа MEGA 5.2. Топология дерева восстановлена при помощи метода присоединения соседей. Эволюционные расстояния рассчитаны с применением метода максимального правдоподобия. До-стоверность оценивалась поср… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, it should be noted that this species constituted the largest number in terms of sample size. Earlier, our research revealed a high percentage of influenza A viruses and avian paramyxoviruses, but ACoV was not included in the studies [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that this species constituted the largest number in terms of sample size. Earlier, our research revealed a high percentage of influenza A viruses and avian paramyxoviruses, but ACoV was not included in the studies [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The role of infected but asymptomatic wild migrating birds in the dissemination of viruses over long distances was first described at the beginning of the 1970s when avian influenza A viruses (AIV) and avian paramyxoviruses (subfamily Avulavirinae, family Paramyxoviridae) (APMV used hereafter for the purposes of this paper) in wild waterfowl were described in multiple publications, including active surveillance in Russia [9][10][11][12][13][14][15][16]. The probability of new zoonotic variants intruding into the human population raises concerns following the history of previous influenza pandemics and recent sporadic fatal cases of avian influenza in humans [17][18][19].…”
Section: Introductionmentioning
confidence: 99%